Design of Clean and Green Smart Visible Communication System with LED/LASER: Exploring LI-Fi: An Innovative Communication System (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With the advancement of the ICT services and their impact in all sphere of life is well acknowledged by the society. Innovation and automationhas developed an advancedcommunicationsystem . Demand and necessity in the acquiredtechnology is uprising vertically andhorizontally in terms of development of the nation andits economy. Today wireless communication has become the integrated part of our life, whether it is professional or personal. With highly increased demand of data , many new service provider have increased significantly and as a result capacity of micro wave spectrum is drying up and interference has become a major problem, in addition of use of microwaves are restricted insome area like aero plane,under water etc.To prototype the frame work of national vide communication channel to meet the demand of the ICT service by the society and the requirement ofEnergy to meet and sustain the frame work of communication Technology.LI-Fi may play an important and vital role to innovate the communicate techniques. LI-Fi Communication Technology has overcomes all the drawbacks of existing Wi-Fi technology.Present paper enlightens the issues and solutionto prove the LI-Fi as one of the pioneer technology and also comparison of different sources used in the same. Li-Fi based on light spectrum so LED and Laser can be used as Source. Both have some pros and cons.We havedone experiment with both and result is summarized.